Assessment of microRNA profile of kidney biopsies of patients with lupus nephritis - Tahereh Malakoutian; Sepideh Hajian; Ahmad Ebrahimi; Koosha Kamali (Society of Diabetic Nephropathy Prevention, 2017)
Background: The changes in some epigenetic elements such as microRNAs result in aberrant immune responses leading to production and secretion of nephritogenic autoantibodies as the main fundament of lupus nephritis (LN). Objectives: The present study aimed to assess the miRNA profile of kidney biopsies in patients with LN with the purpose of describing the critical role of these elements in LN creation. Patients and Methods: In this case-control single center study 11 patients who suffered LN (as the case group) and 11 patients with normal kidney function who were candidate for nephrectomy due to cancer or cyst (as the control group) were included. Kidney biopsies were taken from all LN and control subjects. RNA was extracted and converted to cDNA, then the cDNA was evaluated using NANODROP and then intra-renal expression of candidate miRNAs were quantified in the two groups. In the present study, four topranked miRNAs, miR-638, miR-146a, miR-198, and miR-731 were selected for qRT-PCR. Results: Consistent with the microarray data, we found no significant difference in the expression of all miRNAs between LN and control groups. Using REST 2009 software, we did not also reveal any difference in expression of four miRNAs studied between the patients with LN and those without LN in both parametric and nonparametric patterns. Conclusions: The expression of miR-638, miR-146a, miR-198, and miR-731 may not be related to occurrence of LN in Iranian population.